2021
DOI: 10.7575/aiac.ijkss.v.9n.2p.28
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Bat Handle Sensor for Measuring Bat Velocity, Attack Angle, and Vertical Angle

Abstract: Background: Bat velocity, attack angle, and vertical angle are common variables that coaches and players want to evaluate during their baseball or softball swing. Objective: The purpose of this study was to investigate and validate a baseball bat handle sensor against motion capture using recreational baseball and softball athletes for bat velocity, attack angle, and vertical angle. Methods: This single visit cross-sectional experimental design study utilized eighteen recreational baseball and softball players… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The test result was in the observation place to determine the product's reliability using the percentage formula. According to Arikunto (Stewart et al, 2021), if the data is in percentages, proportions and ratios, the conclusions can be taken and adjusted to the problems. At the field trial stage, the data obtained were also analysed by factor analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The test result was in the observation place to determine the product's reliability using the percentage formula. According to Arikunto (Stewart et al, 2021), if the data is in percentages, proportions and ratios, the conclusions can be taken and adjusted to the problems. At the field trial stage, the data obtained were also analysed by factor analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In summary, the IMUs can accurately measure swing speed over a wide range, but caution should be exercised when evaluating players whose swing speed exceeds 30 m/s. In a single measurement, all IMUs are not accurate enough to analyze the intraindividual changes in both parameters; therefore, the average value of multiple measurements should be used when evaluating the hitting motion in practice [15].…”
Section: Error Causes and Trendsmentioning
confidence: 99%
“…On the other hand, regarding the values measured by IMUs, it has been pointed out that the reliability of the swing speed is high within and between individuals, but the accuracy of the swing angle is low [14]. In addition, a study that used a motion capture system to verify the accuracy of the sensor reported that, although there was a significant correlation between the two measurements, the individual data contained errors [15]. Studies that have validated the accuracy of wireless IMU measurements through video analysis and wire-based sensors have indicated that the swing speed can be measured with high accuracy over a narrow range, but with low accuracy over a wide range [13].…”
Section: Introductionmentioning
confidence: 99%